Rediscovered at last: a new enigmatic genus of Axymyiidae (Diptera) from western North America - Sinclair, Bradley J. (Zootaxa, 2013)
An unusual and undescribed genus and species of Axymyiidae known from a single specimen collected more than 50 years ago in Alaska is rediscovered in Mt. Rainier National Park (USA: WA). Based on two female specimens, Plesioaxymyia vespertina gen. nov., sp. nov. is described. A preliminary phylogenetic tree of the Axymyiidae is presented, showing Ple-sioaxymyia as sister group to all remaining axymyiid genera.